93 Neuropsychological assessment in children with tourette syndrome and chronic tic disorders: do families find this useful and are recommendations implemented?. (4th October 2017) - Maclellan, K; Murphy, T; McFarlane, F; Heyman, I; Stark, D
Abstract : Background: Tourette Syndrome (TS) is a common childhood neurodevelopmental disorder characterised by chronic motor and vocal tics. 1 High-levels of comorbidity are seen in TS, including elevated rates of specific learning disorders, 2 cognitive difficulties and language disorders. 3 Paediatric neuropsychological assessment includes administration of age-standardised tests evaluating cognitive, behavioural and academic functioning; notably identifying cognitive strengths and weaknesses. 4 The findings and recommendations are subsequently communicated to children's families, health and education networks. The purpose of recommendations is to facilitate increased support for the child that includes learning advice and home based activities to improve daily-living. There is paucity in literature on parent and child satisfaction of these assessments, 5, 6, 7 and no identified literature on whether recommendations are implemented. 8, 9 This study aimed to assess levels of satisfaction amongst parents and children with TS following neuropsychological assessment, and investigate the proportion of recommendations implemented at home and school. Method: All children who underwent a neuropsychological assessment in a specialist TS clinic from 2013 – 2016 were identified. Parents and children were asked to complete an anonymous questionnaire adapted from a published questionnaire 6 rating the neuropsychological assessment satisfaction. Follow up telephone contact then identified whether specific recommendations within the report were implemented and if not, what barriers prevented implementation. Results: A response rate of 38% was achieved and both parents and children reported high levels of satisfaction with the assessments. Approximately 60% of recommendations for the home and school were successfully implemented. Barriers preventing implementation into both school and home settings will be presented in full. Conclusion: This study supports the usefulness of paediatric neuropsychological assessments and indicates a high-level of satisfaction from the parent and child perspective. However clinical and educational recommendations for the school appear harder to implement compared to home-based recommendations. Clinical implications for further research are discussed. References: . A Dietrich, TV Fernandez, RA King, JA Tischfield, PJ Hoekstra, GA Heiman. The Tourette International Collaborative Genetics (TIC Genetics) study, finding the genes causing Tourette syndrome: Objectives and methods. European child & adolescent psychiatry 2015;24(2):141–151. . L Burd, RD Freeman, M Klug, J Kerbeshian. Tourette syndrome and learning disabilities. BMC paediatrics 2005;5(1):34. . C Legg, C Penn, J Temlett, B Sonnenberg. Language skills of adolescents with Tourettes syndrome. Clinical linguistics & phonetics 2005;19(1):15–33. . CH Silver, LB Blackburn, S Arffa, JT Barth, SS Bush, SP Koffler, RW Elliott. The importance of neuropsychological assessment for the evaluation of childhood learning disorders: NAN Policy and Planning Committee. Archives of Clinical Neuropsychology 2006;21(7):741–744. . D Stark, S Thomas, D Dawson, E Talbot, E Bennett, A Starza-Smith. Paediatric neuropsychological assessment: An analysis of parents perspectives. Social Care and Neurodisability 2014;5(1):41–50. . D Bodin, JT Beetar, KO Yeates, K Boyer, AN Colvin, S Mangeot. A survey of parent satisfaction with pediatric neuropsychological evaluations. The Clinical Neuropsychologist 2007;21(6):884–898. . JE Farmer, TJ Brazeal. Parent perceptions about the process and outcomes of child neuropsychological assessment. Applied Neuropsychology 1998;5(4):194–201. . LL Cheung, CE Wakefield, SJ Ellis, A Mandalis, E Frow, RJ Cohn. Neuropsychology reports for childhood brain tumour survivors: Implementation of recommendations at home and school. Pediatric blood and cancer 2014;61(6):1080–1087. . SM Kanne, JK Randolph, JE Farmer. Diagnostic and assessment findings: A bridge to academic planning for children with autism spectrum disorders. Neuropsychology review 2008;18(4):367–384.